Criação e implementação de empresa Casa de Chás - Weissheimer, Alberto Zampieri (Universidade do Vale do Rio dos Sinos, 2013)
This document has as main objective to present a project plan for the creation and implementation of an enterprise call Casa de Chás. Through the various areas of knowledge present in the PMBOK, we attempted to provide as best as possible the steps and processes necessary to enable the opening of a store, since its initial strategic planning until such time that it is ready to open its doors to the public. We highlight the practical project management cost, quality, human resources, communications, risk and procurement.
Keywords: Plano de gerenciamento do projeto; Abertura de empresa; Project management plan; Creation of an enterprise